DIGITALISASI DAKWAH KORPS DAKWAH SANTRI (KODASA) PP. DARUSSALAM BLOKAGUNG BANYUWANGI - Obianto, Agung; Iskandar, Hasyim; Hadiono, Abdi Fauji; Maskur, Maskur (International Conference on Humanity Education and Society (ICHES), 2024)
Darussalam Islamic Boarding School is one of the Islamic Boarding Schools located in Banyuwangi, East Java. It was founded in 1951 with the Salaf learning method which is still maintained until now Darussalam Pondok continues to develop with the times. Apart from religious learning taught to students, Islamic boarding schools also focus on developing Islamic da'wah in society. Therefore, the students are given a platform for self-development in the form of a da'wah extracurricular called KODASA Santri Da'wah Corps (KODASA) and digital literacy called Multimedia Darussalam (MMD). It is through this second institution that the Darussalam Blokagung Islamic Boarding School actualizes conventional preaching and digital Da'wah activities. It is against this background that researchers focus their research on da'wah activities carried out by Islamic Boarding Schools to optimize Islamic preaching students in the digital era by looking at the da'wah strategies that have been used in optimizing da'wah activities. The method used in this research is descriptive qualitative in which the researcher tries to understand the meaning of the events that occurred based on the information of the people who experienced them. The results of this research show that the Kodasa and MMD Institutions make students at the Darussalam Blokagung Islamic Boarding School have da'wah skills, both conventional and digital, and the media owned by the Islamic boarding school can be used as a means of da'wah for Darussalam Blokagung students.